Minorities and Multilingualism in India: Language in Education Dr. Prabhu Nath Singh1, and Dr. Ram Murat Verma2 (International Journal of Innovative Research in Engineering & Management, 2023)
It is impossible to fully handle education  in India without taking into account the country's  linguistic and cultural context. This main purpose of this  paper is to provide background knowledge concerning  India's linguistic elements. The term "minorities" is  considered in the context of India, and indeed the extra  clothes by the Indian Constitution for minority  communities is examined. Going to follow that, there is a  consideration on language policy in Indian education, as  well as an analysis of several college course ideas.  Among the relevant areas explored are the variety of  languages taught, the language of instruction, and  curriculum design for residents of minority languages.  The paper will also discuss several linguistic revolutions  and their impact upon Indian education. Language is one  of the most controversial subjects in Indian education.  India, being a democratic, multilingual country and its  educators are always discussing whether tongues should  be exploited as a teaching medium, specifically for  consumers of minority languages with no standard  written forms.
Keywords: Anglo Indians; Constitutional Protection; V; Multilingualism; Minority Language